THE EFFECT OF SLUG TWO-PHASE FLOW ON THE MECHANICAL STRESS BEHAVIOUR OF RIGID PIPELINES - IBRAHIM MOHMMED, ABDALELLAH OMER (2016)
Pipelines are operating in a harsh environment and they are susceptible to internal forces which are exerted by the conveyed multiphase flow. These internal and external conditions make the pipeline design are extremely challenging. Accordingly, this study aims to investigate the Fluid Structure Interaction (FSI) between the slug two-phase flow and solid pipe Experimental and numerical approaches were utilized to address the consequences of slug flow-pipe interaction.